The Influence of Comminuting Methods on the Structure, Morphology, and Calcium Release of Chicken Bones - Wang, Ying; Feng, Tao; Xia, Qiang; Zhou, Changyu; Cao, Jinxuan (Frontiers in Nutrition, 2022)
This work aimed at assessing the influence of comminuting methods, including colloid mill, planetary ball mill and dynamic high-pressure microfluidization on the chemical composition, particle properties, morphology and calcium release of chicken bone. The results showed that both planetary ball mill and dynamic high-pressure microfluidization could reduce the particle size of bone powder, and the particle size of sample treated by dynamic high-pressure microfluidization reached 446 nm. Chicken bone particles were negatively charged and the absolute value of zeta potential was significantly reduced after milling treatments. Furthermore, X-ray diffraction and Fourier transform-infrared spectroscopy analysis indicated that the planetary ball mill and dynamic high-pressure microfluidization processes presented no significant effects on the internal chemical structure of bone particles. Compared with the other groups, samples treated by dynamic high-pressure microfluidization released more calcium ions, related to the significant effects on surface calcium composition and reducing particle size. Therefore, dynamic high-pressure microfluidization has a great potential in the processing of bone-derived products, particularly for the design and development of bone-derived product with high calcium bioaccessibility.